Biomedical Applications of Gold Nanoparticles - Cabuzu, Daniela; Cirja, Andreea; Puiu, Rebecca; Mihai Grumezescu, Alexandru (Current Topics in Medicinal Chemistry, 2015)
Gold nanoparticles may be used in different domains, one of most important being the biomedical field. They have suitable properties for controlled drug delivery, cancer treatment, biomedical imaging, diagnosis and many others, due to their excellent compatibility with the human organism, low toxicity and tunable stability, small dimensions, and possibility to interact with a variety of substances. They also have optical properties, being able to absorb infrared light. Moreover, due to their large surface and the ability of being coated with a variety of therapeutic agents, gold nanoparticles have been showed a great potential to be used as drug delivery systems. Gold nanoparticles are intensively studied in biomedicine, and recent studies revealed the fact that they can cross the blood-brain barrier, may interact with the DNA and produce genotoxic effects. Because of their ability of producing heat, they can target and kill the tumors, being used very often in photodynamic therapy. Gold nanoparticles can be synthesized in many ways, but the most common are the biological and chemical methods, however the chemical method offers the advantage of better controlling the size and shape of the nanoparticles. In this review, we present the principal applications of gold nanoparticles in the biomedical field, like cancer treatment, amyloid-like fibrillogenesis inhibitors, transplacental treatment, the development of specific scaffolds and drug delivery systems.
Keywords: Biomedical applications